2020
DOI: 10.3390/microorganisms8010140
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin-Resistant Salmonella enterica Serovar Kentucky ST198 in Broiler Chicken Supply Chain and Patients, China, 2010–2016

Abstract: Salmonella enterica serovar Kentucky (S. Kentucky) sequence type 198 has emerged as a global zoonotic pathogen. We explored Salmonella enterica serovar Kentucky ST198 samples from the broiler chicken supply chain and patients between 2010 and 2016. Here, we collected 180 S. Kentucky isolates from clinical cases and the poultry supply chain. We performed XbaI pulsed-field gel electrophoresis and multilocus sequence typing. We assessed mutations in the quinolone resistance-determining regions and screened for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 29 publications
2
24
1
1
Order By: Relevance
“…The data suggest that the positivity ratio for S. Kentucky ST198 was lower in China than in Europe (0.5% to 1%) and comparable to that in the United States (0.2%) (4, 5). The higher positivity ratio detected in food isolates than in clinical isolates is consistent with the previous findings that domestic poultry and poultry sources largely contribute to the global spread of ST198 (4,12,13). Additionally, our data showed that ST314 was the second most prevalent subpopulation in S. Kentucky.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The data suggest that the positivity ratio for S. Kentucky ST198 was lower in China than in Europe (0.5% to 1%) and comparable to that in the United States (0.2%) (4, 5). The higher positivity ratio detected in food isolates than in clinical isolates is consistent with the previous findings that domestic poultry and poultry sources largely contribute to the global spread of ST198 (4,12,13). Additionally, our data showed that ST314 was the second most prevalent subpopulation in S. Kentucky.…”
Section: Resultssupporting
confidence: 92%
“…Together, our findings show that the positivity ratio for S. Kentucky ST198 among S. enterica isolates was 0.18% (27/15,405) in China, which is ca. 2-fold lower than that reported in a previous study (0.39% [40/16,247]) (12). This difference could be caused by different regions included in the sample collection.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations